1994
DOI: 10.1063/1.468434
|View full text |Cite
|
Sign up to set email alerts
|

Overtone resonance Raman scattering beyond the Condon approximation: Transform theory and vibronic properties

Abstract: The time correlator formalism is used to develop the expression for nth order (overtone) resonance Raman scattering (RRS) to include both Raman frequency shifts upon electronic excitation as well as non-Condon vibronic coupling. In particular the compact operator formalism recently introduced by Hizhnyakov and Tehver [J. Raman Spectrosc. 19, 383 (1988)] to obtain several RRS correlators (including overtone scattering with frequency shift, but in the Condon approximation) is used to extend the theory. At the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…30 They showed that the overtones appear also through a term that corresponds to the second term of eq 16 under such a condition. 30 This conclusion is readily understood in the framework of eq 16, by considering that the matrix element 〈V f |Q|V i 〉 can have a nonzero value for ∆V > 1 transitions when the potential minima of the i and f electronic states are displaced. With a significant potential displacement, the second term of eq 16 (the Herzberg-Teller coupling) can also give rise to the overtone in the spectra.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 They showed that the overtones appear also through a term that corresponds to the second term of eq 16 under such a condition. 30 This conclusion is readily understood in the framework of eq 16, by considering that the matrix element 〈V f |Q|V i 〉 can have a nonzero value for ∆V > 1 transitions when the potential minima of the i and f electronic states are displaced. With a significant potential displacement, the second term of eq 16 (the Herzberg-Teller coupling) can also give rise to the overtone in the spectra.…”
Section: Discussionmentioning
confidence: 99%
“…For the overtones in the resonance Raman spectra, it is important to note that the appearance of the overtones only indicates the existence of a significant displacement between the S 1 and S n potentials, but it does not directly imply that the Raman intensity arises from the Franck−Condon mechanism. Actually, Albrecht and co-workers reported a general theory of Raman intensities for a situation where both the potential displacement and the non-Condon effect are significant . They showed that the overtones appear also through a term that corresponds to the second term of eq 16 under such a condition .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, time-resolved measurements on hydrogen bonded complexes of C102 with 2,2,2-trifluoroethanol have indicated that the rotation times can be understood as due to long-lived solute−alcohol complexes as a whole . However, it has been mentioned (ref in ref ) that for C102 half of the emission shifts between nonpolar and alcoholic solvents are already present when dealing with 1:1 probe−alcohol complexes. Moreover, as discussed in section 2 of this paper, our results obtained with femtosecond vibrational spectroscopy of hydrogen bonded C102 have unequivocally demonstrated the dynamics of hydrogen bond cleavage within 200 fs after electronic excitation.…”
Section: Femtosecond Optical Spectroscopymentioning
confidence: 99%
“…The effects of reorganization of vibrational degrees of freedom may be another possibility that needs to be inspected more carefully, but, in the light of the experimental results presented previously 54 and in this paper, these effects should then lead to a change of electronic state. If one would assume that the electronic state remains the same after optical excitation of C102, one can only explain the ultrafast components in pump−probe and grating scattering experiments by assuming a time-dependent electronic transition moment (in other words, the Condon approximation does not hold). So far there is no indication for such an effect in resonant excitation of large dye molecules such as C102 in the literature. Additional photon echo experiments in full resonance with the aborption band of C102−(phenol) 1,2 in C 2 Cl 4 could give information on this issue.…”
Section: Femtosecond Optical Spectroscopymentioning
confidence: 99%
“…An alternative approach to evaluating resonance Raman intensity data is the “transform theory” method, originally developed by Page and co-workers and since refined and extended by others. The transform method exploits the close similarity between optical absorption and resonance Raman scattering to show that, under certain approximations, the band shape of the resonance Raman excitation profile can be expressed as a simple function of the Kramers−Kronig transform of the absorption spectrum. Comparison of the band shapes of the experimental and predicted profiles thus can be used to determine the validity of the assumptions made in the analysis, and the overall scaling of the profiles can provide relative, and in some cases absolute, values for the displacements.…”
Section: Resonance Raman Intensitiesmentioning
confidence: 99%